URINARY DIVERSION AFTER RADICAL CYSTECTOMY, ORTHOTOPIC NEOBLADDER VS ILEAL CONDUIT: A SYSTEMATIC REVIEW AND META-ANALYSIS OF POSTOPERATIVE COMPLICATION - Fahri, Muhammad; Gampo Alam Irdam (Indonesian Urological Association, 2023)
ABSTRACT Objective: The purpose of this study is to compare orthotopic neobladder (ONB) and ileal conduit (IC) formation in terms of surgical outcome and complication. Material & Methods: Computerized bibliographic search on different databases related to this study. The PICO criteria method was applied to define research eligibility, per PRISMA recommendations and conducted a systematic review of the literature with meta-analysis. Weighted mean differences with 95 percent confidence intervals were used to compare continuous outcomes. Results: There were 479 publications were discovered and only 6 studies fulfilled the criteria included. The random-effect model's pooled result for urinary leakage complication revealed a significant difference of 1.62 between ONB and IC with higher incidence in neobladder group (95 percent CI, 1.85, 8.69, P = 0.0004) with non-significant heterogeneity (Chi2 = 0.65, df = 3 (P = 0.89), I2 = 0%). Other complications (ileus complication, anastomosis site stenosis, sepsis, urinary infection) showed non-significant difference. Conclusion: Because of the heterogeneity in several aspects of the analyzed papers, further study comparing Orthotopic Neobladder and Ileal conduit in terms of complication following urinary diversion are needed to conﬁrm superiority of ONB or IC as the urinary diversion of choice. Keywords: Orthotopic neobladder, ileal conduit, urinary diversion, radical cystectomy